Integrated assessment of mucilage impact on human health using the One Health approach: Prevalence and antimicrobial resistance profiles of Escherichia coli and Clostridium perfringens in the Marmara Sea, Türkiye - Artun Yibar; Hilal Ay; Fuat Aydin; Secil Abay; Emre Karakaya; Tuba Kayman; Cem Dalyan; Fatih Dogan Koca; Duygu Aydogdu; Nihed Ajmi; Muhammed Duman; Izzet Burcin Saticioglu (Heliyon)
This study employed a One Health approach to assess the potential impact of mucilage on human health by characterizing the prevalence and antimicrobial resistance (AMR) profiles of Escherichia coli and Clostridium perfringens strains isolated during the 2021 mucilage event in the Marmara Sea, Türkiye. Mucilage, a gelatinous organic substance exacerbated by climate change, disrupts marine ecosystems by depleting oxygen, threatening biodiversity, and serving as a reservoir for pathogenic microorganisms. Surface and benthic mucilage samples collected from the Marmara Sea were analysed for AMR profiles using genome analysis, the BD Phoenix™ 100 automated system, and E-test methods. The study identified 13 E. coli and one C. perfringens strain, harboring 244 and six AMR genes from 21 and eight drug classes, respectively, along with multiple virulence factors (VFs). The E. coli strains exhibited four distinct serotypes (O138:H28 [Mu-3], O18:H49 [Mu-4], O128:H12 [Mu-35] and O101:H10 [Mu-125]), reported for the first time from Türkiye and mucilage. Notably, anaerobic microorganisms like C. perfringens thrived in mucilage, underscoring their ecological significance. Seasonal and climatic factors influencing mucilage formation amplify its role in transmitting antimicrobial-resistant pathogens, posing significant risks to public and environmental health. The findings highlight the urgent need for continuous monitoring and mitigation strategies for mucilage-related hazards.